Engineering and characterizing hydrogel fibres for biomedical applications - Toh, Augustine Wei Lun (Nanyang Technological University, 2021)
Hydrogels have been used for biomedical applications and their effectiveness has been studied and proven for many years. There are many key characteristics of hydrogels that are desired and thus being researched to optimize these characteristics. However, the field of study for hydrogel is overly broad, and must be narrowed down into specific areas to be further researched. In this study, the main hydrogel of focus is alginate, and some characteristics of alginate that make it desirable. Some of these include optimizing the structure of a hydrogel tube, which is a fibre with a hollow inner cavity, to simulate a blood vessel, or increasing the surface roughness of the alginate hydrogel to improve on the adhesiveness of the alginate fibre. Multiple methods of producing a hydrogel tube were explored, and in this study, the potential use of a different structure, such as a hydrogel fibre within a hydrogel tube was also tested. Biocompatibility of the alginate hydrogel was also tested, and the results show that while alginate composites have good biocompatibility, cells are unable to adhere to hydrogels that are made with solely alginate, due to the lack of a rougher surface texture for adhesiveness.